Quantification of hematopoietic stem and progenitor cells by targeted DNA methylation analysis - Ledio Bocova; Wouter Hubens; Cordula Engel; Steffen Koschmieder; Edgar Jost; Wolfgang Wagner (Clinical Epigenetics, 2023)
Abstract Hematopoietic stem and progenitor cells (HSPCs) are quantified in daily clinical practice by flow cytometry. In this study, we provide proof of concept that HSPCs can also be estimated by targeted DNA methylation (DNAm) analysis. The DNAm levels at three individual CG dinucleotides (CpG sites) in the genes MYO1D, STK17A, and SP140 correlated with CD34+ cell numbers in mobilized peripheral blood and with blast counts in leukemia. In the future, such epigenetic biomarkers can support the evaluation of stem cell mobilization, HSPC harvesting, or blast count in leukemia.